2016
DOI: 10.1080/02699206.2016.1179344
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the role of executive functions in preschoolers’ phonological development

Abstract: There is limited yet compelling evidence that domain-general processes may contribute to speech sound change. This study explored whether executive functions contribute to the achievement of adult-like speech production. Children who are 4 to 5 years old, 42 with high-average speech production skills, 11 with low-average and nine with speech sound disorder (SSD), participated in a battery of executive function and speech production tasks. Performance accuracy was compared across groups and also correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Many previous investigations documenting the interrelatedness between language and EF abilities have placed particular emphasis on higher order aspects of language (e.g., fluency, receptive, and expressive abilities, language representation, and sentence comprehension) ( Montgomery, 1995 ; Trainor, 2012 ; Engelhardt et al, 2013 ; Miller and Marcovitch, 2015 ), or have relied on transcription methods to measure speech accuracy in relation to cognitive performance-based EF measures ( Eaton and Ratner, 2016 ). These studies have suggested that more proficient language abilities are associated with stronger EF skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous investigations documenting the interrelatedness between language and EF abilities have placed particular emphasis on higher order aspects of language (e.g., fluency, receptive, and expressive abilities, language representation, and sentence comprehension) ( Montgomery, 1995 ; Trainor, 2012 ; Engelhardt et al, 2013 ; Miller and Marcovitch, 2015 ), or have relied on transcription methods to measure speech accuracy in relation to cognitive performance-based EF measures ( Eaton and Ratner, 2016 ). These studies have suggested that more proficient language abilities are associated with stronger EF skills.…”
Section: Discussionmentioning
confidence: 99%
“…As we can see, there have been numerous reports evidencing a relation between language and EF abilities, but to our knowledge only one study has examined speech articulation proficiency in relation to EF. In a study investigating EF and phonological development in 4- to 5-year-olds, Eaton and Ratner (2016) aimed to address whether EF contributes to adult-like speech production abilities. Children with SSD and children with low-average and high-average speech skills took part in a battery of assessments.…”
Section: Introductionmentioning
confidence: 99%
“…As described in other studies, a good development of WMP is important for the development of speech and oral language (LINASSI; KESKE-SOARES; MOTA, 2005;GRAY, 2006;VIEIRA, 2014) suggest that children with speech errors may have less mature working memory than peers who have mastered phonological targets earlier in development (TORRINGTON EATON;RATNER, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, failures in the system can cause damage in the development of speech and oral language, in lexical acquisition, in the process of learning, reading and understanding a text and in resolving mathematic problems (MAJERUS; VRANCKEN; VAN DER LIDEN, 2003 NAVAS, 2008;NEVO;BREZNITZ, 2013;GUEDES-GRANZOTTI et al, 2013;CARDOSO;SILVA;PEREIRA, 2013;TORRINGTON EATON;RATNER, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Murphy and colleagues (2014) showed that children with speech sound disorders committed more false alarms than controls, on an auditory attention task, because of the lower inhibitory control and/or selective attention. Eaton and Ratner (2016) explored the relation between phonological development and some executive functions (working memory, inhibitory control, and cognitive flexibility) in 4-to 5-year-olds children. They found that children with better performance on digit span task had better speech sound production.…”
Section: Introductionmentioning
confidence: 99%